A Triad of Complete Dorsal Pancreatic Agenesis, Pancake Kidney and Bicornuate Uterus. An Association or an Incidental Finding: First Case in Literature - Lal, Anupam; Pavunesan, Santhosh Kumar; Mahalingam, Harshavardhan; Garg, Mandeep; Sinha, Saroj K; Khandelwal, Niranjan (JOP. Journal of the Pancreas, 2015)
Context Agenesis of the dorsal pancreas is a rare congenital anomaly which can be detected either incidentally during imaging or encountered during investigation for pancreas related pathologies such as pancreatitis or diabetes mellitus. Few associations of this condition with heterotaxy syndrome, pancreatic tumors and congenital heart disease have been described. Case report We report a novel association of genitourinary anomalies in a case of complete dorsal pancreatic agenesis not previously described in the literature. Conclusion Knowledge about dorsal pancreatic agenesis is essential for radiologist in patients presenting with unexplained pain abdomen and its association with various conditions may help radiologist in assisting clinician in management of these patients. Image: Two horns of bicornuate uterus (arrows) and kidney in pelvis.